Enhancing Arabic textbook utilization effectiveness: a perspective of Mnemonic strategies (using CaMrY) - Hj. Yaakub, Muhamadul Bakir; Osman, Nurulhuda; Abu Bakar, Radhwa; Sahrir, Muhammad Sabri (2011)

(untitled)
Enhancing Arabic Textbook Utilization Effectiveness (EATUE) is a courseware project designed specifically for users’ of Arabic Textbook, such as students, teachers and even an interested third-party in dealing or utilizing or examining a textbook as a source of teaching and learning material in a classroom setting. The issue of effectiveness here is not new, even though it is crucial. Therefore, this courseware is constructed as an attempt to presents an electronic and multimedia application as an evaluation tool and methodology in enhancing the degree of effectiveness in which a user supposes to be benefited from a textbook. This will be obtain through measuring the user’s ability in reflecting the most important contain of a textbook based on mnemonic strategies in retrieving and sustaining its primary information. In other words, it will provide exhaustive indication on how to differentiate between two sets (or more) Arabic textbook proposed in a classroom setting or how to enhance the effectiveness of usage for a specific textbook been chosen for a classroom which is expected or assumed to be a better source of information needed by student in and outside the classroom. For that purposes, mnemonic strategies will be utilised to provide an indicator for the most effective textbooks (in range) or a set of action proposal in enhancing a specific textbook used in a particular setting.